Caste in History - Banerjee-Dube,Ishita (Oxford, 2008)
This volume, a part of the prestigious Themes in Indian History series, brings together the work of distinguished scholars on the analyzing caste and related socio-cultural processes. There are anthropological and ethnological collections on the issue of caste but this volume through acollection of seminal essays brings together the much-needed historical perspective on the issue.A comprehensive introduction sets the tone for the consideration of the questions of caste. Beginning with the period of the coming of the Portuguese to India, the collection of essays considers caste in medieval and modern times. It brings together the ethno-sociological categories of study such asthe census and village-community with the political and the historical-colonialism, nationality, and state-formation. The question is approached from both the macro-perspective considering prominent leaders, the national movement, and British imperialism as well as through micro-studies ofspecific communities and their practices. These wide-ranging topics are divided in four subsequent sections- Caste and Colonialism, Caste in Practice, Caste and Politics, and Caste in Everyday Life - the questions are considered from these various dimensions. Eminent contributors like Bernard Cohn,Frank Conlon, Eleanor Zelliot, Shail Mayaram, Shekhar Bandopadhyay's works feature in this volume along with several other equally incisive and readable essays. This volume will be indispensable for any collection or consideration related to the issue of caste.